Tenure of independent directors and analysts following: Moderating role of institutional ownership - Chin Sok Fun; Nor Shaipah Abdul Wahab; Tye Wei Ling; Premagowrie Sivanandan; Nurliyana Haji Khalid (Cogent Business & Management, 2023)
This study examines the impact of tenure of independent directors on analyst following, and the moderating role of institutional ownership between tenure of independent directors and analyst following. The data utilized in this study was collected from 3,656 firm-years of Malaysian public listed firms from 2013 to 2020. By employing Huber-White adjusted t-statistics to analyse the data using the STATA software, this study finds that short-tenured independent directors are preferred by analysts and the relationship is significantly moderated by institutional ownership. This study has significant ramifications on theory, policy, and practice. Theoretically, this study provides further evidence to support the executive cognition theory, social capital theory and stakeholder theory. In the perspective of policy, policy makers gather feedback on the implementation of a beneficial corporate governance practice by restricting the tenure of independent directors. Practically, market players with conservative risk appetite are encouraged to invest in firms, which are closely scrutinized by institutional shareholders, thus, ensuring enhanced corporate governance and accountability.
Keywords: 650; analysts following; corporate governance; independent director; institutional shareholders; Malaysia; tenure